Plato and the establishment of mathematics as a science - Gaiser, Konrad (Revista Archai, 2011)
This paper deals with the establishment of mathematics as a science in the doctrine of Plato. Specifically, it deals with the fusion of two themes ”“ ontological differentiation and the mathematical-dimensional gradational hierarchy between the opposing Principles ”“ which results in a fundamental Platonic conception: the possibility of harvesting the fundamental analogy between ontological structure (from appearances to Ideas) and the system of mathematical structural laws, creating a reciprocal relationship of illumination and foundation between mathematics and ontology.